HUBUNGAN TINGKAT STRES DENGAN KETIDAKTERATURAN MENSTRUASI PADA REMAJA PUTRI DI SMAN 1 KAMPAR KIRI - - Mutiara, Sherly; Situmorang, Masriani (Journal of Hospital Administration and Management (JHAM), 2023)
The World Health Organization (WHO) reports that out of 18 million women aged 18-55 years have menstrual cycle disorders, As for menstrual cycle disorders, the most common menstrual cycle disorder is irregular menstrual frequency of 80.7%. Basic Health Research data states that in Indonesia women aged 10-59 years who experience regular menstruation are 68% and who have irregular menstrual problems in 1 year as much as 13.7%. Irregular menstrual problems at the age of 17-29 years and the age of 30-34 years are quite a lot, which is 16.4%. The reason stated by women aged 10-59 years who have irregular menstruation due to stress and a lot of thoughts is 5.1%. Stress is known to be the causative factor of the occurrence of menstrual irregularities. The impact of menstrual irregularities is that it becomes more difficult to conceive (Infertility), then it also makes it difficult for women to find when the fertile period is and not. To determine the relationship between stress levels and menstrual irregularities in young women at SMAN 1 Kampar Kiri. This type of research is a correlation study that explains the relationship between variables. Meanwhile, the research design uses cross sectional. This research was conducted in June-July 2023 at SMAN 1 Kampar Kiri. The total sample in this study was 59 respondents with the inclusion of female students who were willing to be respondents and were not suspected of being pregnant. Irregular menstrual cycles were higher in respondents with moderate stress levels of 80%, compared to very severe stress levels of 75%, mild 57.1%, normal 29.6% and severe 25%. Meanwhile, the regular menstrual cycle was higher in respondents whose stress level was severe by 75%, compared to normal stress levels of 70.4%, mild 42.9%, severe sanga 25%, and moderate 20%. From the results of the Chi Square statistical test, a p-value of 0.029 was obtained. This shows that the p-value of < 0.05, then H1 is accepted which means that there is a significant relationship between stress levels and menstrual cycles in young women at SMAN 1 Kampar Kiri.